Analisis Manajemen Sarana dan Prasarana di SD Negeri 060857 - Andre Jonatan; Amos Gultom; Jian Sitanggang (Dinamika Pembelajaran : Jurnal Pendidikan dan bahasa, 2025)
This study aims to analyze the management of educational facilities and infrastructure at SD Negeri 060857 through interviews with the principal, teachers, and students. The main focus includes aspects of adequacy, efficiency, and effectiveness of school facility management in supporting learning. The interview instrument for the principal focuses on strategic planning, evaluation, and technology integration in management. For teachers, it focuses on perceptions of the adequacy of facilities and involvement in the managerial process. Meanwhile, for students, the interview explores direct experiences of the comfort and quality of the available facilities. The results of the study are expected to provide a holistic picture as a basis for improving the management of facilities and infrastructure to be more planned, efficient, and sustainable in supporting quality education.